PENGARUH PARTISIPASI PEJABAT STRUKTURAL PADA KINERJA MANAJERIALPEMERINTAH KOTA DENPASAR - Made Wahyu Adhiputra (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2015)
Globalization era leads to change in the concept of regional autonomy that requires granting greater authority to the regions at the level of districts, mainly in development and provision of better public services. To be able to carry out the development and provision of better public services, it is demanded an increase in civil service performance, particulary as the motor of structural officials of government agencies in carrying out its duties and functions. The performance known as menegerial performance may improve if the structural official are actively involved or participated in the budgetary process, couple with high organizational commitment, profesinalim and organizational structure in accordance with the needs. Based on the description above, the formulation of the problems in this research are: (1) Does Structural Officers Participation positivrly influence the Managerial Perfoemance, (2) Does the organizational have a positive commitment on Managerial Performance, (3) Does Profesionalis of Structural Officer positively on Managerial Performance; and (4) whether the organizational strukture positively effect on Managerial Performance. The purposes of this research are: (1) to provide empirical evidence that participation of structural officials positively influence the managerial performance; (2) to provide empirical evidence that organizational commitment positively influence the managerial performance; (3) to provide empirical evidence that profesionalis positively influence the managerial performance; (4) to provide empirical evidence that organizational structure positively influence the managerial performance. Proportional stratified random sampling method was applied in taking the samples of this study, whilw the data was collected using a survey nethod accompanied with questionnaire technique. The target respondents of this research are 64 respondents. Testing validity and reliability of the instrument variables used in this study have a high level of acceptability. The result of the research shows synthesis that the better the structuralofficer participation is, the better the organizational commitment becomes, themore adequate the professionalism and the more appropriate the organizationalstructure are, the managerial performance of the Government of Denpasar will beincreasing. The influence of Organizational structure on managerial performanceis more dominant than the structural official participation of organizationalcommitment and profesionalism. Keywords: Managerial performance, Participation on structural officials,Commitment organizational, Profesionalism and organizationalstructure.